Energy and cost for pelleting and transportation of select cellulosic biomass feedstocks for ethanol production - Wilson, Jonathan M.; McKinney, Leland J.; Theerarattananoon, Karnnalin; Ballard, Todd C.; Wang, Donghai; Staggenborg, Scott A.; Vadlani, Praveen V. (My University, 2014)
The current forage handling equipment in the cellulosic ethanol industry is severely limited by the low bulk density of baled and ground biomass. Low bulk density contributes to flowability problems and lack of maximizing trailer capacities. Biomass pelleting process can improve the bulk density and flowability characteristics of forages. The objectives of this research were to evaluate: (1) the energy requirements of grinding sorghum stalks, corn stover, wheat straw, and big bluestem through two different screen size openings, (2) the energy requirements of pelleting forages from the two grind sizes, (3) the physical properties of pelleted biomass, and (4) the costs associated with biomass processing, transportation, and storage. The two mill screen size openings (3.2 and 6.5 mm) were found to have significantly different energy consumptions for grinding step from each other. All four forage types, except for big bluestem and corn stover, were also found to have significantly different energy consumptions for grinding. Production rate through the 6.5 mm screen was almost three times higher than that of the 3.2 mm screen (average of 181.4 vs. 68 kg/h). Hammermill screen size opening (i.e., grind size) was found to have significant effects on energy consumption for pelleting process. The four forage types were also found to have significantly different energy consumptions from each other, except for big bluestem versus wheat straw (P=0.1192). Particle length for the 3.2 mm grind ranged from 0.15 to 0.18 cm, while the 6.5-mm grind ranged from 0.20 to 0.31 cm. Pelleting increased bulk density from 99.96 to 160.02 kg/m³ for raw biomass grinds to 499.30 to 701.13 kg/m³ for pelleted biomass. Pellet durability ranged from 93% to 98%. A cost analysis indicated that it would take roughly $22 extra per metric ton for the transportation, pre-processing, and storage of pelleted cellulosic biomass than corn grain. This cost is still almost half that of the cost for baled biomass.
Keywords: Biomass pellets; Bulk density; Cellulosic ethanol; Electrical energy; Logistics